Depressive Mindstyle and Reader Inference in Illness Memoirs: A Cognitive Stylistic Comparison of Joan Didion and Matt Haig - Mamona Yasmin Khan; Farah Fatima (Indus Journal of Social Sciences, 2025)
The exploration of depressive thought patterns encoded by literary memoirs is undertaken through the lens of cognitive stylistics, specifically focusing on the framework of mindstyle. The study applies Fowler's fundamental theory and the developments of Semino and Stockwell to examine Joan Didion's Blue Nights and Matt Haig's Reasons to Stay Alive. The narrative voice, lexis, metaphor, and syntactic patterns all influence the mental states associated with despair and sorrow. The study examines how readers can mimic sadness through the use of metaphors related to darkness, immobility, and isolation using mindstyle analysis, conceptual metaphor theory, and schema theory. Haig's dialogic method and Didion's introspective, fragmentary writing contrast demonstrates the impact of stylistic devices on ethical engagement and emotional inference. The selected texts resist mental health conventions while guiding readers through schematic illness tales. This multidisciplinary approach, drawing from affective stylistics, medical humanities, and literary studies sheds light on the empathetic potential of autobiographical writing and the linguistic representation of psychological pain.